Meeting Market and Societal Ambitions with New Robust Grape Varietals: Sustainability, the Green Deal, and Wineries’ Resilience - Marc Dressler (Agriculture)
This study investigates the sustainability impact of fungus-resistant grape varieties within viticulture, addressing economic, ecological, and social dimensions. Pesticide management is of paramount importance for wineries but causes additional costs, impairs sustainability, and faces societal non-acceptance. Digital monitoring of four German wineries for two consecutive years allowed us to compare treatments of traditional and robust varietals. The results demonstrate that the latter enables a significant reduction in pesticide treatments, can be key for copper reduction, and is of paramount importance for organic winemaking. By reducing pesticide dependency, lowering operational costs, hedging risks, and improving labor efficiency, FRW present a key to sustainable viticulture. The results suggest that robust varietals present a means to comply with societal pressure and to meet EU Green Deal ambitions. This paper contributes new, practice-oriented knowledge on FRW’s role in sustainable viticulture, confirming both the ecological and economic advantages in real-world settings, alongside unique insights into social sustainability and market positioning strategies. Sustainability impact is quantified, and a newly introduced productivity metric allows for the orchestration of resilience. The findings contribute to the discourse on sustainable agriculture by validating FRW as a strategic response to climate and regulatory pressures, resilience, and competitive positioning.